Neurosurgical Emergencies at a Tertiary Referral Center in a Sub-Saharan African Country - ALIHONOU, THIERRY; Kisito, Quenum; PADONOU, ADEBOLA; AMOSSOU, FRANCOIS; dossou, francis (My University, 2020)
Background The practice of neurosurgery in a teaching hospital requires modern diagnostic tools and a rigorous organization of care. Objectives To present and discuss the management of neurosurgical emergencies in a teaching hospital in poor and low-income country. Patients and Methods This is a retrospective and descriptive study from April 2015 to March 2017 and includes traumatic and nontraumatic neurosurgical emergencies. Epidemiological, diagnostic, operative, and outcome data were evaluated. Results During the study period, 397 cases of neurosurgery were admitted. One hundred seventy-five of them were emergencies (43%), including 168 (96%) of traumatic origin. The average age was 32.5 years (1–80 years) with a male predominance: 149 men for 26 women, the sex ratio was 6.68. The cause of the neurotraumatological emergency was mostly road accidents with 143 cases (85.1%). The trauma was brain injury in 155 patients (92.3%) and spine injury in 13 patients (7.7%). In 64.3% of cases, diagnostic imaging was done beyond 48 hours. Surgery time was more than 48 hours when it was performed (21 cases). Outcome was good for 19 patients. Overall and postoperative mortality were, respectively, 34.5% (58 cases) and 9.5% (2 cases). Conclusion Neurosurgical emergencies care at the Departmental Teaching Hospital of Ouémé–Plateau has become a common activity with encouraging operating results despite difficult practice conditions
Keywords: trauma; spine; emergencies; neurosurgery